Systemic Lupus Erythematosus: Molecular Mimicry between Anti-dsDNA CDR3 Idiotype, Microbial and Self Peptides—As Antigens for Th Cells - Aas-Hanssen, Kristin; Thompson, Keith M.; Bogen, Bjarne; Munthe, Ludvig A. (Frontiers in Immunology, 2015)
Systemic lupus erythematosus (SLE) is marked by a T helper (Th) cell dependent B cell hyperresponsiveness, with frequent germinal center reactions, and gammaglobulinemia. A hallmark of SLE is the finding of IgG autoantibodies specific for dsDNA. The specificity of the Th cells that drive the expansion of anti-dsDNA B cells is unresolved. However, anti-microbial, anti-histone and anti-idiotype Th cell responses have been hypothesized to play a role. It has been entirely unclear if these seemingly disparate Th cell responses and hypotheses could be related or unified. Here we describe that H chain CDR3 idiotypes from IgG+ B cells of lupus mice have sequence similarities with both microbial and other self peptides, matched sequences were increased within the mutated CDR3 repertoire and when sequences were derived from lupus mice with expanded anti-dsDNA B cells. Analyses of histone sequences showed that particular histone peptides were similar to VDJ junctions. Moreover, lupus mice had Th cell responses towards histone peptides similar to anti-dsDNA CDR3 sequences. The results suggest that Th cell in lupus may have multiple cross-reactive specificities linked to the IgVH CDR3 Id-peptide sequences as well as similar DNA-associated protein motifs.